Antibacterial Activities of Wasabi against Escherichia coli O157:H7 and Staphylococcus aureus - Lu, Zhongjing; Dockery, Christopher R.; Crosby, Michael; Chavarria, Katherine; Patterson, Brett; Giedd, Matthew (Frontiers in Microbiology, 2016)
Escherichia coli O157:H7 and Staphylococcus aureus are two of the major pathogens frequently involved in foodborne outbreaks. Control of these pathogens in foods is essential to food safety. It is of great interest in the use of natural antimicrobial compounds present in edible plants to control foodborne pathogens as consumers prefer more natural “green” foods. Allyl isothiocyanate (AITC) is an antimicrobial compound naturally present in wasabi (Japanese horseradish) and several other edible plants. Although the antibacterial effects of pure AITC and wasabi extract (essential oil) against several bacteria have been reported, the antibacterial property of natural wasabi has not been well studied. This study investigated the antibacterial activities of wasabi as well as AITC against E. coli O157:H7 and S. aureus. Chemical analysis showed that AITC is the major isothiocyanate in wasabi. The AITC concentration in the wasabi powder used in this study was 5.91±0.59 mg/g. The minimum inhibitory concentration (MIC) of wasabi against E. coli O157:H7 or S. aureus was 1% (or 10 mg/ml). Wasabi at 4% displayed higher bactericidal activity against S. aureus than against E. coli O157:H7. The MIC of AITC against either pathogen was between 10 and 100 µg/ml. AITC at 500 µg/ml was bactericidal against both pathogens while AITC at 1000 µg/ml eliminated E. coli O157:H7 much faster than S. aureus. The results from this study showed that wasabi has strong antibacterial property and has high potential to effectively control E. coli O157:H7 and S. aureus in foods. The antibacterial property along with its natural green color, unique flavor, and advantage to safeguard foods at the point of ingestion makes wasabi a promising natural edible antibacterial plant. The results from this study may be of significant interest to the food industry as they develop new and safe foods. These results may also stimulate more research to evaluate the antibacterial effect of wasabi against other foodborne pathogens and to explore other edible plants for their antimicrobial properties. To our knowledge, this is the first report on the antibacterial activity of wasabi in its natural form of consumption against E. coli O157:H7 and S. aureus.